Beberapa AspekTentang Upaya Menempatkan Kepentingan Masyarakat di dalam Pengelolaan Hutan - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2000)
Sustainable"multiyieWforestmanagemenhtasbeena longconsideration of forestersandbecomea maincomponent of forestry,althoughtheconceptand objectivemaychangein lhe changein socialvalue,economicdevelopment and populationincrease. Thereis astrongdemandthatforestactivitiesbeshiftedto a morepeoplecenteredbasedforestry: amoreoffensiveapproachtowardpeople'swelfareisneeded insteadof thedefensiveone.As faras forestryconcern,it willtakea littletimefor foresterto understandtherealmeaningof thenewparadigm,whichalsoinvolves traditionatel chnicaklnowledgienforestryworkss, inceunlikefolksworkinginagriculture, thetraditional-foresthearsbeenequippedwithlesssocialdisciplinesT. hisarticledescribesomeaspectsofputtingpeople'